EMPOWERMENT OF FISHERY CULTIVATOR GROUP (POKDAKAN) SEPAKAT AT SIANJUR MULAMULA DISTRICT, SAMOSIR REGENCY - Evy Sinaga; Adianto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Community empowerment is an effort to make the community independent through the realization of the potential capabilities possessed by the community. As the Fisheries Division of the Agriculture Service of Samosir Regency did to a group of people in Singkam Village who are members of the fish cultivator group (Pokdakan) to improve the community's ability to cultivate fish as an effort to improve the community's economy. This study aims to describe the implementation of empowerment and the inhibiting factors for implementing pokdakan in Singkam Village, Sianjur Mulamula District, Samosir Regency. This type of research is a descriptive research with a qualitative approach. Data was collected using field observations, interviews, and documentation of both primary and secondary data. The results of this study indicate that: 1) The implementation of the empowerment of the fish cultivator group (pokdakan) Sepakat in Singkam Village has not been able to lead group members to independence. 2) The inhibiting factor for implementing pokdakan empowerment is the lack of capacity in the Fisheries Division of the Samosir Regency Agriculture Service as an empowerer both in terms of human resources and budget. Different characters and thoughts become obstacles in group development. Selfishness and laziness are still often encountered in group members, so they do not actively participate in group activities.